MENINGKATKAN HASIL BELAJAR PECAHAN SEDERHANA MATA PELAJARAN MATEMATIKA MELALUI CONTEXTUAL TEACHING AND LEARNING PADA SISWA KELAS III MIN KERTAK HANYAR II KABUPATEN BANJAR - Abdussatar Abdussatar (Al-Adzka: Jurnal Ilmiah Pendidikan Guru Madrasah Ibtidaiyah, 2016)
Material about simple fractions administered to students, because this material is part of the mathematical sciences are a lot of benefits, such as counting the parts of the whole of an object or objects. This research uses a method of a class action with the goal of improving student learning outcomes in completing simple fraction by applying contextual teaching and learning approach. For the subject of this study were all students of class III MIN Kertak Hanyar II, Banjar Regency, which amounted to 32 people consisting of 18 male students and 14 female students in the second semester of the school year 2013/2014. The research instrument used in this class action is the observation of activities of teachers in the learning process, student activity observation in the learning process, and a written test. The data collection technique using the technique achievement test, observation, while the percentage of data analysis using the technique. Results of research conducted shows of student learning activities individually to complete a simple fraction declared successful and the learning objectives achieved. It is known from the results of the second cycle. The first meeting of the first cycle of the average value of 66.25 increased to 69.06 at the second meeting of the first cycle, the second cycle the first meeting of the average value of 78.13 increased to 84.37 at the second meeting of the second cycle. With the increase in the value of an average of 66.25 at 69.06 at the first meeting and the second meeting of the first cycle increased to 78.13 at 84.37 at the first meeting and the second meeting of the second cycle, shows the average above indicators minimal mastery learning for Mathematics is 70.00. Likewise, the observation of the activity of the teacher and student activity observation also increased, it is known from the results of the second cycle. Teacher activity increased with the percentage of the first cycle of 84% to 92% in the second cycle, and student activity increased with the percentage of the first cycle of 80% to 86.6%. This means the application of contextual teaching and learning approach can improve student learning outcomes in completing simple fractions in mathematics learning in class III MIN Kertak Hanyar II, Banjar.